2017
DOI: 10.4172/1948-593x.1000174
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of In Vitro Antidiabetic and Antioxidant Activities and Preliminary Phytochemical Screening of Leaf Extracts of Avicennia officinalis

Abstract: Avicennia officinalis is a medicinal mangrove plant and used in traditional folk medicine for treatment of various ailments. In the present study, the antidiabetic and antioxidant activities of petroleum ether and aqueous extracts of leaves of A. officinalis were evaluated. The antidiabetic activity was evaluated out by α-amylase and α-glucosidase inhibition study and antioxidant capacity by DPPH, superoxide and hydrogen peroxide scavenging activity of leaf extracts at various concentrations. The maximum antid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Notably, the aqueous leaf extract exhibited superior inhibition of these enzymes compared to the petroleum ether extract. [33]…”
Section: Anti-diabetic Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, the aqueous leaf extract exhibited superior inhibition of these enzymes compared to the petroleum ether extract. [33]…”
Section: Anti-diabetic Activitymentioning
confidence: 99%
“…Furthermore, petroleum ether and aqueous leaf extracts showcased antioxidant capacity in assays targeting DPPH, superoxide, and hydrogen peroxide scavenging, with IC50 values ranging from 0.17 to 0.27 mg/ml. Additionally, ethanol extracts from both bark and leaf demonstrated a dose-dependent scavenging capacity against superoxide radicals, DPPH, and ABTS, with IC values ranging from 82 to 207.6 µg/ml [36,50,51] .…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…This plant's stem or bark is used traditionally as diuretic, antiulcer, therapy for snakebite, rheumatism, skin conditions, hepatitis, antitumor, antibacterial, gastroprotective, boils, and abscesses. Pharmacological studies have demonstrated the antibacterial, antiulcer, anti-inflammatory, anti-cancer, and antioxidant activities of several Avicennia officinalis leaf and bark extracts (Bhimba et al, 2010;Kumar et al, 2017;Ngoc-Van et al, 2022). The majority of this plant's distribution is in Malaysia, Bangladesh, India, and Indonesia.…”
Section: Introductionmentioning
confidence: 99%